The Influence of Halal Awareness and Halal Certification on the Purchase Decisions of Korean Instant Noodles Among Teenage Consumers in Surabaya - Abharul Lubbi; Ulya Sarofa (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The halal food industry is a major sector in Indonesia, supported by a predominantly Muslim population. On the other hand, imported food products such as Korean instant noodles are attracting the interest of domestic consumers, particularly among teenagers. Instant noodles are a fast-food item that is very popular among teenage consumers, especially with the rise of the Korean Wave in Indonesia. However, not all Korean instant noodles available in Indonesia are halal-certified. Muslim consumers must be more discerning when selecting Korean instant noodle products before making a purchase, starting with their own awareness. This study aims to analyze the influence of halal awareness and halal certification on the purchasing decisions of teenage consumers in Surabaya regarding Korean instant noodle products. The analysis method used was Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. Data was collected from 200 teenage respondents in Surabaya using a closed-ended Likert scale questionnaire. The results of the study indicate that halal awareness and halal certification significantly influence the decision to purchase Korean instant noodle products among teenage consumers in Surabaya. Halal awareness has a coefficient value of 0.311 (t-statistic 4.008; p-value 0.000), while halal certification has a coefficient value of 0.452 (t-statistic 5.956; p-value 0.000). This indicates that halal certification has a greater influence than halal awareness on the purchasing decisions of Korean instant noodles among teenage consumers in Surabaya